ANÁLISE DE SOBREVIVÊNCIA APLICADA A DADOS DE REINCIDÊNCIA AO CRIME - ZANON, Matheus Henrique Pimenta; BARROS, Emílio Augusto Coelho (Brazilian Journal of Biometrics, 2018)
The Brazilian prison system is a point of great discussion in our current political and social moment. The last report (DEPEN, 2014) points out that Brazil is the fourth country with the largest number of individuals deprived of their freedom in the world, esteemed although the rate of recidivism to crime for males is around 50% and for females is 35%. This work was based on the SECAT database information of the city of Primeiro de Maio-PR, Brazil, containing 356 individuals, covering the period from December 2009 to December 2015. Our event of interest is recidivism crime of each individual during the observation period. To conduct this study, we are suggesting to use survival analysis techniques due to the fact that it contains censored observations. This paper advocate the use of distribution Burr XII with and without fraction of cure, besides the Weibull distribution with and without cure rate for modeling and analysing the data, since there is evidence that many individuals have never faced the event of interest. To obtain the estimators of the proposed models, we have considered the frequentist and Bayesian inference approaches.